Fractional Order Sliding Mode Control of PMSG-Wind Turbine Exploiting Clean Energy Resource - Khan, Muhammad Waseem; Wang, Jie; Xiong, Linyun; Ma, Meiling (International Journal of Renewable Energy Development, 2019)
The extensive application of permanent magnet synchronous generator (PMSG) based wind energy conversion system (WECS) has attracted growing interests of power researchers on its control and operation. This paper aims to propose a kind of fractional order sliding mode based (FOSM) power output control scheme of PMSG based WECS with fast exponential reaching law (FERL). The FERL based FOSM control technique proves to be better capable of attenuating the level of the chattering phenomenon with faster convergence speed. The boost converter and the neutral point clamped inverter, both of which are utilized to connect the PMSG and the power grid, are controlled with the proposed FOSM control scheme. Furthermore, the direct and quadrature grid current are tracked, which leads to the control of the active and reactive power output. The effectiveness of the proposed method is verified with an 8kW wind turbine simulation and the test results indicate that the proposed method can better track the reference value of active and reactive power. In addition to that, the total harmonic distortion level of the grid current is largely mitigated.Â©2019.CBIORE-IJRED. All rights reservedArticle History: Received June 2ndÂ  2018; Received in revised form October 6th 2018; Accepted January 7th 2019; Available onlineHow to Cite This Article: Khan, M.W., Wang, J., Xiong, L. and Ma, M. (2019). Fractional Order Sliding Mode Control of PMSG-Wind Turbine Exploiting Clean Energy Resource. International Journal of Renewable Energy Development, 8(1), 81-89.https://doi.org/10.14710/ijred.8.1.81-89